Prevalensi dan Risk Assessment Kejadian Hipertensi pada Petani Wanita di Desa Sumowono: Prevalence and Risk Assessment of Hypertension in Female Farmers in Sumowono Village - Alfan Afandi; Sri Lestari (Universitas Ngudi Waluyo, 2023)
The number of hypertension events in Sumowono Sub-district in 2023 was 888 events. Most of the population of Sumowono Subdistrict works in the agricultural sector. This study aims to determine the factors associated with the incidence of hypertension in farmers. This type of research is observational analytic with cross sectional approach design. The sample in this study was 59 female farmers who were taken using accidental sampling technique. Data collection on risk factors was done through interviews, while the prevalence of hypertension was done through blood pressure checks. The results of the study of 59 respondents showed 26 respondents were categorized as hypertensive, 11 people were pre-hypertensive, and 22 people had normal blood pressure. Of the 37 people who still have normal blood pressure and pre hypertension, 11 people have a low risk, 18 people have a moderate risk, and 8 people have a high risk of suffering from hypertension in the future. The conclusion of this study is that the prevalence of hypertension in farmers is 37.3%, and 48.6% have a moderate risk of developing hypertension. Research advice, hypertension risk control is needed from related health services, as well as active screening efforts so that it can detect early the risk of hypertension in farmers. ABSTRAK Jumlah kejadian hipertensi di Kecamatan Sumowono tahun 2023 adalah 888 kejadian. Sebagian besar penduduk Kecamatan Sumowono bekerja di sektor pertanian. Penelitian ini bertujuan untuk menggambarkan prevalensi dan risk assessment kejadian hipertensi pada petani di Desa Sumowono. Jenis penelitian ini adalah analitik observasional dengan rancangan pendekatan cross sectional. Sampel dalam penelitian ini adalah 59 petani berjenis kelamin perempuan yang diambil menggunakan teknik accidental sampling. Pengumpulan data faktor risiko dilakukan melalui wawancara, sedangkan prevalensi hipertensi dilakukan melalui pemeriksaan tekanan darah. Hasil penelitian terhadap 59 responden menunjukkan 26 responden termasuk dalam kategori hipertensi, 11 orang pra hipertensi, dan 22 orang mempunyai tekanan darah normal. Dari 37 orang yang masih memiliki tekanan darah normal dan pre hipertensi tersebut, didapatkan 11 orang memiliki risiko rendah, 18 orang risiko sedang, dan 8 orang berisiko tinggi untuk menderita hipertensi di kemudian hari. Kesimpulan penelitian ini adalah prevalensi hipertensi pada petani sebesar 37,3%, dan 48,6% memiliki risiko sedang mengalami hipertensi. Saran penelitian, diperlukan pengendalian risiko hipertensi dari pelayanan kesehatan terkait, serta upaya screening aktif sehingga bisa mendeteksi secaradini resiko terjadinya hipertensi pada petani.